2003
DOI: 10.1046/j.1464-410x.2003.04017.x
|View full text |Cite
|
Sign up to set email alerts
|

The number of lymph nodes examined and staging accuracy in renal cell carcinoma

Abstract: OBJECTIVE To determine the number of lymph nodes that need to be examined to accurately stage the pN variable in patients undergoing radical nephrectomy (RN) for renal cell carcinoma (RCC). PATIENTS AND METHODS We reviewed the operative and pathology reports of 725 patients with RCC submitted for RN. All tumours were classified using the fifth edition of the Tumour‐Nodes‐Metastasis classification. For each patient the number of lymph nodes removed was recorded. The patients were divided into five different gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 25 publications
(62 reference statements)
3
61
0
4
Order By: Relevance
“…110 In view of this, it is of interest that the number of N þ nodes has been shown to be higher in those cases where greater numbers of lymph nodes are sampled and it has been recommended that 412 nodes be examined for staging purposes. 111 In validation studies of the N category of the 2002 TNM classification, it was found that there was no difference in the survival rate of pN1 and pN2 tumors at 5 years follow-up (20 and 17%, respectively). 112 When cases were divided at r4 and 44 involved nodes, the difference in survival between the two groups was significant.…”
Section: Lymph Node Metastasesmentioning
confidence: 98%
“…110 In view of this, it is of interest that the number of N þ nodes has been shown to be higher in those cases where greater numbers of lymph nodes are sampled and it has been recommended that 412 nodes be examined for staging purposes. 111 In validation studies of the N category of the 2002 TNM classification, it was found that there was no difference in the survival rate of pN1 and pN2 tumors at 5 years follow-up (20 and 17%, respectively). 112 When cases were divided at r4 and 44 involved nodes, the difference in survival between the two groups was significant.…”
Section: Lymph Node Metastasesmentioning
confidence: 98%
“…Amerikan Kanser Ortak Komisyonu (AJCC) patolojik N evrelemesinin yapılabilmesi için değerlendirilen bölgesel LND örneğinin 8 ve daha fazla lenf nodu içermesi gerektiğini bildirirken Terrone ve ark. ise RN ve LND yapılan her evreden 608 RHK olgusunu değerlendirdikle-ri çalışmalarında 13'den az lenf nodu çıkarılan grupta patlojik N+ olgu oranı %10.2 iken 13 ve üzeri lenf nodu çıkarılan grupta bu oranın %20.8'e yükseldiğini göster-mişlerdir (p<0.001) [19].…”
Section: Rhk'de Lenf Nodu Tutulumunu öNgörebilen Belirteç-lerunclassified
“…The incidence of occult positive lymph nodes is 3%-5% in patients with cT1-2 N0M0 tumours and 10%-20% with cT3-4 N0M0 tumours. 17 After proper preoperative staging, the incidence of unsuspected lymph node metastases is low (about 3%).…”
Section: Role Of Lymphadenectomymentioning
confidence: 99%
“…However, important prognostic information for patients with locally advanced disease may be obtained. 17 Lymphadenectomy should be restricted to the perihilar tissue for staging purposes in patients with stage N0M0. Extended lymphadenectomy has not been demonstrated to improve survival in these patients.…”
Section: Role Of Lymphadenectomymentioning
confidence: 99%